Behavioural characterisation of the robotic mouse mutant. - Oliver, P; Keays, D; Davies, K (2007)
The ataxic mouse mutant robotic is characterised by progressive adult-onset Purkinje cell loss that occurs in a distinctive region-specific pattern. We report the first behavioural characterisation of this mutant and quantify its performance on tests of motor function, locomotor and exploratory activity over a time course that reflects specific stages of cell loss in the cerebellum. Robotic mutants are significantly impaired on the rotarod and static rod tests of coordination and their performance declined during aging. In addition, gait analysis revealed an increase in the severity of the ataxia displayed by mutants over time. Interestingly, spontaneous alternation testing in a T-maze was not significantly affected in robotic mice, unlike other ataxic mutants with more rapid and extensive cerebellar degeneration; robotic therefore provides an opportunity to investigate the necessity of specific Purkinje cell populations for various behavioural tasks.